Factor Analysis of Student Financial Literacy Level On Investment in the Islamic Capital Market - Ananda Putri Salsabilla (Business Finence Analyst Co.,, 2023)
Broadly speaking, the capital market is a place where sellers and buyers of shares interact to raise funds. Companies sell securities to investors interested in potential returns. Islamic capital markets, which adhere to the principles of Islamic finance, are increasingly in demand as an investment option, but understanding of them still needs to be improved, especially among university students.Islamic capital markets are a crucial part of an economy based on Islamic justice and morality, but investment literacy in this regard is still low among university students. An understanding of sharia principles and market analysis are key focal points in investment literacy, especially to encourage active participation from students. In the face of the challenges of digitalization, an in-depth understanding of the principles of Islamic capital markets is crucial to ensure equitable financial inclusion.The objective of this study is to analyze the factors that influence students' investment literacy in Islamic capital markets. With a better understanding of these factors, it is expected that more effective educational strategies can be designed to increase students' understanding and participation in investing in accordance with sharia principles. In doing so, it is expected to contribute positively to sustainable and ethical economic growth in the future.